The Influence of Knowledge Management and Competence on Employee Performance through Organizational Commitment as an Intervening Variable in Management of BUMDES in Sidoarjo Regency - Chandra Pratama Rulidha; Sigit Hermawan (Proceedings of The ICECRS, 2021)
Sustainability of Village Business Entity (VBE) depends on human resources for managing organization, considering this organization needs ambidextrous management towards a social business oriented. Reserch purpose to examine the effect of Knowledge Management and Competence on Employee Performance through Organizational Commitment as an Intervening Variable in Management of VBE in Sidoarjo. Research method is quantitative, research techniques is path analysis and questionnaire. The results showed knowledge management doesn’t increase organizational commitment, competence doesn’t increase organizational commitment, knowledge management has an increasing employee performance, competence has an increasing employee performance, organizational commitment doesn’t increase employee performance, organizational commitment as an intervening variable doesn’t increase knowledge management on employee performance, organizational commitment as an intervening variable doesn’t increase competence on employee performance, organizational commitment as an intervening variable doesn’t increase knowledge management and competence on employee performance. Suggestions for VBE in Sidoarjo is consistently improve employee performance through knowledge management and competence.